Economy and subsistence in the Early Neolithic site of Carrascal (Oeiras, Portugal) - Cardoso, João Luís (2021)
Early Neolithic settlements in southwestern Iberia are rare and, so far, only a few faunal assemblages, mostly from Portuguese Estremadura, have been analysed. The zooarchaeological studies suggest that animal husbandry was introduced to the area by Neolithic marine settlers originating from the Mediterranean and that domesticated animal herding, particularly sheep, was of outmost importance to the human communities. Located in lower Estremadura, Carrascal is an open-air site, featuring several dwelling structures, a diversified set of artefacts, and a well-established chronology for its Early Neolithic occupation (cal BC). It also yielded a faunal assemblage of considerable size and variability, which includes vertebrates (mammals and fishes) and invertebrates (molluscs). The present study, which focuses on the vertebrate materials, shows that during Early Neolithic the community that inhabited Carrascal practiced a diversified set of subsistence activities in which animal husbandry was prevalent. There is an abundance of caprines (mainly sheep) and swine, followed by cattle. The age at death data suggests a mixed animal exploitation system, with swine being mostly killed at a younger age (presumably for meat), while cattle was slaughtered after reaching adulthood (perhaps for milk production) and caprines show a mixed pattern. This study also reinforces the idea that, for the Neolithic communities living in lower Estremadura, hunting was a less prevailing activity (aurochs and, perhaps, wild boar were identified, but red deer is absent in Carrascal) when compared with the human groups that lived in the central Estremadura Limestone Massif, a situation that may be due to different ecosystems and human demography.